DYNAMIC CAPABILITIES AND COMPETITIVE ADVANTAGE IN ISLAMIC FINTECH: EVIDENCE FROM INDONESIA - Anna Sardiana (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to examine how Islamic fintech firms in Indonesia develop and utilize dynamic capabilities to achieve competitive advantage. It addresses the limited attention given to Shariah-compliant fintech within existing literature and highlights the need to understand how firms integrate technological innovation with regulatory and ethical requirements in a rapidly evolving financial landscape. A qualitative multiple-case study approach was employed, involving 10 Islamic fintech firms registered under the Financial Services Authority (OJK) in Indonesia. Data was collected through semi-structured interviews with key decision-makers, including executives and managers. The data were analyzed using thematic analysis based on the dynamic capability framework, focusing on sensing, seizing, and reconfiguring processes. The results reveal that Islamic fintech firms build competitive advantage through three core dynamic capabilities. Sensing involves market intelligence and regulatory awareness; seizing is reflected in innovation, customer-centric strategies, and collaboration; while reconfiguring emphasizes continuous learning and talent development. These capabilities translate into key advantages, including Shariah compliance, transparency, financial inclusion, operational efficiency, and agility.  The study is limited by its qualitative design, small sample size, and reliance on firm-level perspectives, which may affect generalizability. Future research could adopt quantitative methods, including broader stakeholders, and conduct cross-country comparisons. This study extends dynamic capability theory into the underexplored context of Islamic fintech and highlights the strategic role of Shariah compliance as a source of competitive advantage. It provides practical insights for firms, policymakers, and researchers in supporting the sustainable growth of the Islamic fintech ecosystem.